A spotlike edge state in plane Poiseuille flow. Issue 1 (December 2014) - Zammert, Stefan; Eckhardt, Bruno
Abstract We study the laminar turbulent boundary in plane Poiseuille flow at Re=1400 and 2180 using the technique of edge tracking. For large computational domains the attracting state in the laminar‐turbulent boundary is localized in spanwise and streamwise direction and chaotic. (© 2014 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)